Returns to Education in the Public and Private Sectors: Europe and Central Asia - Claudio Montenegro; Harry A. Patrinos (Institute of Labor Economics (IZA), 2022)
The returns to schooling are estimated for 28 European and Central Asian countries using the Mincerian function. Our results show that while the public sector pays on average more than the private sector, the effect of education on earnings is stronger in the private sector. However, the returns to tertiary education are higher in the private sector.
Keywords: I21; J31; 330; returns to education; wage differentials; public–private; Europe